Highly Conducting and Flexible Radical Crystals. (16th July 2020) - Kwon, Taeyeon; Koo, Jin Young; Choi, Hee Cheul
Abstract: Together with high conductivity, high flexibility is an important property required for next generation organic electronic components. Both properties are difficult to achieve together especially when the components are crystalline because of the intrinsic high brittleness of organic molecular crystals. We report an organic radical crystal system that has both high flexibility and high conductivity. The crystal consists of 9, 10‐bis(phenylethynyl)anthracene radical cation (BPEA .+ ) units, and shows flexibility under pressure with high conductivity in ambient condition exhibiting average conductivity of 2.68 S cm −1 when normal linear shape, as well as 2.43 S cm −1 when bent. The structural analysis reveals that both a short π–π distance (3.290 Å) between BPEA .+ units that are aligned along the crystal length direction, and the presence of PF6 − counter ions induce flexibility and high electrical conductivity. Abstract : Flexible and radical : 9, 10‐bis(phenylethynyl)anthracene radical cation (BPEA .+ ) crystals obtained by electrocrystallization showed high electrical conductivity and are flexible. Their flexibility is a result of close packing and the help of the hydrogen bonding of the electrolyte anions which allows them to act as mechanical ball‐bearings.